The Effect of Financial Distress, Profitability, Company Size and Growth Opportunity on Prudence Accounting (Case Study on Goods and Consumer Sector Companies Listed on the Indonesia Stock Exchange for the Period 2018-2021) - Rachmad Fajar Muktiono; Mujiyati (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to examine the effect of Financial Distress, Profitability, Company Size, and Growth Opportunity on Prudence Accounting. This study focuses on goods and food companies listed on the Indonesia Stock Exchange. This study uses secondary data from annual financial reports from the official website of the Indonesia Stock Exchange and the websites of each company. The research methodology used is multiple regression analysis using SPSS 2025 software. The research findings show that Financial Distress, Profitability, and Company Size affect Prudence Accounting, while Growth Opportunity does not affect Prudence Accounting.